Analysis of Steady Radiative MHD Nanofluid Flow in a Porous Medium: Effects of Magnetic Field, Prandtl Number, and Internal Heat Source/Sink - Mohammed Garba; Garba Adamu Tahiru; Abubakar Assidiq Hussaini (Mikailalsys Journal of Mathematics and Statistics, 2026)
This study presents a numerical investigation of steady magnetohydrodynamic (MHD) nanofluid flow under the combined effects of thermal radiation, Prandtl number, porous medium permeability, magnetic field strength, and internal heat generation or absorption. The objective is to examine how these governing parameters influence velocity profiles, temperature distributions, and surface heat transfer characteristics. The nonlinear partial differential equations describing coupled momentum and energy transport were reduced to a system of dimensionless ordinary differential equations through suitable similarity transformations and solved numerically. The results show that thermal radiation and internal heat generation substantially increase the temperature field, while momentum transport is suppressed due to intensified thermal–magnetic interactions and resistive forces. An increase in the Prandtl number reduces thermal diffusion and produces thinner thermal boundary layers. Higher porous medium permeability introduces porous resistance that decelerates the flow but enhances surface heat transfer through boundary layer thinning. The applied magnetic field also regulates both momentum and thermal transport through Lorentz forces. Mathematically, these trends are consistent with the structure of the dimensionless governing equations and boundary conditions, indicating strong nonlinear coupling among diffusion, convection, radiation, porous drag, and electromagnetic effects. The study concludes that surface heat transfer performance, represented by the Nusselt number, is primarily governed by wall temperature gradients. These findings contribute to the numerical understanding of MHD nanofluid transport in porous media and provide a useful theoretical basis for applications involving thermal regulation and heat transfer enhancement.